Solid-state fermentation—a sustainable future technology in aquafeeds? - Kalaiselvan, Pandi; Devi, Ng Chinglembi; Deepti, Mutum; Devi, Arambam Ashwini; Akamad, Kamil; Dheeran, Panneerselvam; Debbarma, Sourabh; Vadivel, Dhivakar; Rajesh, Deepan (Frontiers in Marine Science, 2025)
Food waste is considered as a critical global issue in food production, leading to environmental and economic consequences. Repurposing food industry by-products for animal feed can reduce waste, lower feed costs, and improve sustainability in aquaculture. Solid-state fermentation (SSF) has emerged as a promising biotechnological approach to enhance the nutritional value of these by-products. SSF employs microorganisms such as fungi, yeasts, and bacteria to convert low-value agro-industrial residues into bioactive-rich, digestible feed ingredients. This process reduces anti-nutritional factors (ANFs) like phytic acid and tannins, commonly found in plant-based meals, while producing beneficial enzymes and organic acids that support gut health and nutrient utilization. Compared to conventional methods, SSF is energy-efficient, produces minimal wastewater, and aligns well with circular bioeconomy principles. Although fishmeal and soybean meal remain dominant protein sources in aquafeed, their sustainability issues call for alternatives. SSF derived ingredients improve feed efficiency, growth, and immunity in aquatic species, offering a viable substitute. However, challenges remain in optimizing microbial strains, fermentation conditions, and substrate safety. This review discusses SSF’s mechanisms, benefits, and applications in aquafeed, highlighting recent advances, current limitations, and future directions for establishing SSF as a sustainable solution in modern aquaculture feed development.